Transurethral injection of polyacrylamide hydrogel (Bulkamid(®)) for the treatment of female stress or mixed urinary incontinence - Martan, Alois; Masata, Jaromir; Svabík, Kamil; Krhut, Jan (European journal of obstetrics, gynecology, and reproductive biology, 2014)
OBJECTIVE: The aim of this study was to evaluate the cure effect of a transurethral injection (TUI) of Bulkamid(®) for female urodynamic stress (USI) and stress-predominant mixed urinary incontinence. The hypothesis was that the cure effect of Bulkamid(®) is positive in patients who have undergone previous unsuccessful anti-incontinence surgery and in patients with ISD (Intrinsic Sphincter Deficiency). STUDY DESIGN: This retrospective clinical study was performed on 52 patients for whom previous anti-incontinence surgery had failed (n=40) and on patients with ISD. Five patients had a reinjection of Bulkamid(®). The efficacy of TUI was evaluated an average of 22 months (minimum - 6 months, maximum - 50 months) after the procedure. Subjective assessment of the leakage of urine was based on the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-UI SF). Objective assessment of leakage of urine was assessed by the cough test. The cure effect of procedures was evaluated by VAS (Visual Analog Scale: VAS score 0-100; 100 - without leakage of urine, dry) and by using the five-point Likert scale. The statistics were calculated using the software STATISTICA 10-StatSoft. Inc software (Tulsa, USA). RESULTS: A retrospective study was performed on 52 women with urinary incontinence (stress 43, mixed 9), and 51 patients completed the study. One patient with SUI died during the study. Their mean age was 70 years, mean body mass index (BMI) was 28.65, and mean parity was 1.76. Objective assessment by cough test showed that 19.6% of patients had negative results for this test 22 months after the operation. Subjective assessment by the ICIQ-UI SF questionnaire showed that 15.7% of patients were completely dry, while 45.1% of patients were dry or improved. The mean VAS score was 51.3, and on the Likert scale the cure effect was evaluated as 5 or 4 ("cured" or "improved") in 54.9% of patients. CONCLUSIONS: The hypothesis that the cure effect of Bulkamid(®) is positive in patients who have undergone previous unsuccessful anti-incontinence surgery, and in patients with ISD, was confirmed. The procedure is an option for failed anti-incontinence surgery or for patients with ISD.
Keywords: Female stress urinary incontinence; Acrylic Resins; retrospektivní studie; urgentní inkontinence; akrylové pryskyřice; Hydrogels; Urinary Incontinence, Stress; Urinary Incontinence, Urge; Urethra; Aged; senioři; hydrogely; stresová inkontinence moči; Bulkamid(®); injekce; lidé; ženské pohlaví; Injections; Humans; uretra; Retrospective Studies; Female; Bulking agent; Anti-incontinence surgery